DETERMINATION OF RELATIONSHIP BETWEEN SIZE AND LOCATION OF GASTROINTESTINAL LIPOMA ON PLAIN CT SCAN WITH SYMPTOMATOLOGY AND COMPLICATIONS: A RETROSPECTIVE STUDY AT TERTIARY CARE HOSPITAL: Gastrointestinal Lipoma on Plain CT Scan - Khan, Ateeque Ahemed (Pakistan Armed Forces Medical Journal, 2014)
Objective: To determine the frequency, size and location of different types of gastrointestinal (GIT) lipomas on plain CT scan and diagnostic accuracy of CT scan in diagnosis of lipoma.Study Design: Descriptive study.Place and Duration and Study: Radiology department, Civil Hospital and Dow University of Health Sciences, Karachi, from Jan 2010 to Jun 2012.Methodology: This descriptive study was conducted in Radiology department of a tertiary care hospital in Karachi. All cases of CT scan which showed fat containing lesions in GIT were included in study. In all cases, CT scan abdomen was performed due to any other intra abdominal pathology. Diagnosis of lipoma was based on homogenous hypodensity of lesion with CT number (Hounsfield units) corresponding to fatty lesion.Results: A total of 45 cases were selected for this study. Among these, 40 patients under-went follow up CT scan abdomen performed after 1-3 years and showed no change in size, shape and remained asymptomatic as far as lipomas were concerned. In 13 (28.9%) cases of small intestinal lipoma, four cases showed multiple lipomas. Nine cases had lipomas in ileum and 6 cases showed lipomas in jejunal loops. In 19 (42.2%) cases of large bowel lipomas, seven cases showed multiple lipomas. In 8 (17.8%) cases, lipoma was identified in stomach. In five (11.1%) cases, esophageal lipoma was diagnosed on CT scan. In three cases lipoma identified intramurally while submucosal in two cases. All cases showed smooth homogenously hypodense well define lesions with fat density range of -30 HU to -140 HU. All lesions were ovoid to spherical in shape. Size of lesions ranged 1-3.5 cm. No lipoma irrespective of its location, size and shape, was associated with ulcer, bleeding, obstruction, intussusceptions. All patients were asymptomatic and devoid of complications.Conclusion: Diagnosis of GIT lipoma can be reliably made on plain CT scan without going for endoscopic or surgical biopsy for histopathology. The size and location of lipoma were neither associated with symptoms of patients nor complications. Lipomas also remained stable in respect to size, shape, appearance and density on follow up study. Keywords : , .